Combined gating and trafficking defect in Kv11.1 manifests as a malignant long QT syndrome phenotype in a large Danish p.F29L founder family. (17th November 2015) - Kanters, Jørgen K.; Skibsbye, Lasse; Hedley, Paula L.; Dembic, Maja; Liang, Bo; Hagen, Christian M.; Eschen, Ole; Grunnet, Morten; Christiansen, Michael; Jespersen, Thomas
Abstract : Background . Congenital long QT syndrome (LQTS) is a hereditary cardiac channelopathy characterized by delayed ventricular repolarization, syncope, torsades de pointes and sudden cardiac death. Thirty-three members of five apparently 'unrelated' Danish families carry the KCNH2:c.87C> A; p.F29L founder mutation. Methods and Results . Linkage disequilibrium mapping with microsatellites around KCNH2 enabled us to estimate the age of the founder mutation to be approximately 22 generations, corresponding to around 550 years. Neighbouring-Joining analysis disclosed one early and three later nodes. The median QTc time of the carriers was 490 ms (range: 415–589 ms) and no difference was seen between the different branches of the family. The mutation is malignant with a penetrance of 73%. Ten F29L carriers received implantable defibrillators (ICDs) (median age at implant 20 years), and of those four individuals experienced eight appropriate shocks. Patch-clamp analysis in HEK 293 cells, performed at 34°C disclosed a loss-of-function phenotype with fast deactivation, reduced steady-state inactivation current density and a positive voltage shift in inactivation. Western blotting of HEK 293 cells transfected with KCNH2:WT and KCNH2:c.87C> A revealed a reduced fraction of fully glycosylated hERG:p.F29L suggesting that this mutation results in defective trafficking. Conclusion. The altered channel gating kinetics in combination with defective trafficking of mutated channels is expected to result in reduced repolarizing current density and, thus, a LQTS phenotype.